Measurements of differential cross sections for associated production of a W boson and jets in proton-proton collisions at root s=8 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2017)
Differential cross sections for a W boson produced in association with jets are measured in a data sample of proton-proton collisions at a center-of-mass energy of 8 TeV recorded with the CMS detector and corresponding to an integrated luminosity of 19.6 fb(-1). The W bosons are identified through their decay mode W ->mu nu. The cross sections are reported as functions of jet multiplicity, transverse momenta, and the scalar sum of jet transverse momenta ( H-T) for different jet multiplicities. Distributions of the angular correlations between the jets and the muon are examined, as well as the average number of jets as a function of H-T and as a function of angular variables. The measured differential cross sections are compared with tree-level and higher-order recent event generators, as well as next-to-leading-order and next-to-nextto-leading-order theoretical predictions. The agreement of the generators with the measurements builds confidence in their use for the simulation of W+ jets background processes in searches for new physics at the LHC.
Keywords: TO-LEADING ORDER; PLUS JETS